An Optoneuronic Device with Realistic Retinal Expressions for Bioinspired Machine Vision. (19th February 2020) - Berco, Dan; Ang, Diing Shenp; Zhang, Hai Zhong
Abstract : Bioinspired Machine Vision In article number 1900115, Dan Berco, Diing Shenp Ang, and Hai Zhong Zhang demonstrate a bipolar‐mode, nanoscale, optoneuronic device. The device is shown to function in a similar manner to spiking cone photoreceptors and conjugated retinal cells under illumination and in darkness. It can be used as a building‐block for futuristic bio‐inspired, intelligent vision systems able to capture and process visual information.